Comparison between a crank-drive reciprocating compressor and a novel oil-free linear compressor - Liang, K; Stone, R; Hancock, W; Dadd, M; Bailey, P (Elsevier, 2014)
Reciprocating compressors, driven by induction motors through a crank mechanism, have been commercially used over many years for refrigeration. An oil-free linear compressor driven by a moving magnet motor was designed, for a refrigeration system with a compact heat exchanger. Measurements using nitrogen are reported here to compare the motor performance and overall efficiencies of the two types of compressor with comparable design parameters. The experimental results show that the moving magnet linear motor has a much higher motor efficiency than the conventional induction motor, particularly at low power inputs. However, with a much smaller clearance volume (approaching zero), the crank-drive compressor demonstrates a higher volumetric efficiency based on the swept volume, that is approximately 20% higher than the linear compressor when operated at its maximum stroke (13 mm). It is anticipated that with a revised design, the overall performance of the linear compressor could be enhanced further.